Polyamide resin composition, film and film laminate comprising same, and pellet mixture
By using a polyamide resin composition with a specific ratio, the problem of poor compatibility when reusing the polyamide and polyolefin laminates is solved, and the effects of high transparency, strong pinhole resistance and material reuse are achieved.
Patent Information
- Application Number
- CN202380051224.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-04
- Filing Date
- 2023-07-04
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, when the laminated bodies formed by different resins such as polyamide and polyolefin are reused, poor compatibility leads to a decrease in physical properties, and the addition of a compatible agent may cause problems such as thin film gel and reduced transparency.
Using a polyamide resin composition containing aliphatic polyamide resin, an alpha-olefin copolymer with functional groups and other components, the transparency, puncture strength and pinhole resistance of the film are improved by adjusting the component ratio and molecular structure in the composition. and realize the reuse of materials.
The film with excellent transparency, puncture strength and pinhole resistance of films are achieved, and can be effectively reused by material.
Smart Images

Figure BDA0005221032920000361 
Figure BDA0005221032920000371 
Figure BDA0005221032920000401
Abstract
Description
Technical Field
[0001] The present invention relates to a polyamide resin composition, a film and a film laminate comprising the same, and a pellet mixture. Background Art
[0002] In recent years, the reuse of plastic waste has been expected due to global warming, marine pollution problems, etc. In order to impart functions, packaging materials such as food packaging are mostly laminates formed by different kinds of resins such as polyamides and polyolefins. When considering the reuse of these waste materials, it is possible to consider peeling between layers and separating them, but it is technically difficult and unrealistic. On the other hand, when it is reused as it is in the form of a laminate without peeling, due to the poor compatibility of different kinds of resins, the physical properties of the mixed resin after reuse are significantly reduced, and the use is extremely limited. In order to make different kinds of resins mix well, it is possible to consider using a compatibilizer. As a compatibilizer for polyamides and polyolefins, it is known to be a modified ethylene / α-olefin copolymer.
[0003] Patent document 1 discloses a structure which is a multilayer structure comprising a polar layer of nylon and a polyolefin layer, wherein the polyolefin layer contains a compatibilizer component, wherein the compatibilizer component contains an anhydride and / or carboxylic acid functionalized ethylene / α-olefin copolymer having a specific melt viscosity and density, and shows that waste of the multilayer structure can be recycled.
[0004] Patent document 2 discloses a laminate having a sealing layer and a reinforcing layer, wherein the sealing layer contains a compatibilizer, which is a linear low-density polyethylene and an unsaturated carboxylic acid-modified polyolefin, and the reinforcing layer contains a polyamide resin, and the recyclability of the laminate is improved.
[0005] Patent Document 3 discloses a polyamide resin composition comprising 100 parts by mass of polyamide (A) and a density of 0.915 to 0.975 g / cm 3 The acid-modified polyethylene (E) is contained in an amount of 3 to 30 parts by mass and exhibits excellent heat aging resistance and is suitable for automobile parts.
[0006] Patent document 4 discloses a polyamide resin compound, which is prepared by mixing (A) a masterbatch and (B) a polyamide resin in a ratio of 1 / 99 to 60 / 40 (weight ratio), wherein the (A) masterbatch is prepared by melt-mixing (a) a polyamide resin and a modified ethylene-α-olefin copolymer in a ratio of 40 / 60 to 99 / 1 (weight ratio), and it is shown that the polyamide film obtained by molding the compound has excellent pinhole resistance and transparency, and less fisheye generation.
[0007] Patent Document 5 discloses a pelletizable thermoplastic polymer composition comprising (a) a polyamide and (b) a polymer obtained by polymerizing maleic anhydride and an olefin, and shows that the composition can provide a product having improved durability and the like.
[0008] Patent Document 6 discloses a masterbatch composition comprising an olefin-maleic anhydride copolymer and one or more carrier resins for preparing a polyamide compound from a polyamide, and shows that the masterbatch composition has good compatibility and does not undergo phase separation.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application No. 2018-502743
[0012] Patent Document 2: Japanese Patent Application Publication No. 2020-11415
[0013] Patent Document 3: Japanese Patent Application Publication No. 2019-38938
[0014] Patent Document 4: Japanese Patent Application Publication No. 2000-109685
[0015] Patent Document 5: Japanese Patent Application No. 2014-503003
[0016] Patent Document 6: Japanese Patent Application No. 2015-525813 Summary of the invention
[0017] Problem that the invention aims to solve
[0018] It is believed that by including a compatibilizer in the laminate, the recyclability of the laminate waste is improved. Patent Documents 1 and 2 only disclose that the polyolefin layer contains a compatibilizer, but do not disclose that the polyamide layer contains a compatibilizer. Generally speaking, if a compatibilizer such as a modified polyolefin is contained in the polyamide, problems such as film gelation and reduced transparency will occur.
[0019] Patent Document 3 discloses a polyamide resin composition comprising polyamide and acid-modified polyolefin. The polyamide resin composition is intended for use in automobile parts, but is difficult to apply to packaging materials such as food packaging where problems such as the generation of film gel and a decrease in transparency are difficult to solve.
[0020] The film obtained from the polyamide resin compound of Patent Document 4 exhibits certain pinhole resistance, transparency, and reduction of film gel, but the levels are not sufficient. Furthermore, the recyclability of waste is not considered and the recyclability is also insufficient.
[0021] The films obtained from the compositions of Patent Documents 5 and 6 have insufficient physical properties such as film gel, and the recyclability of laminates formed of different types of resins such as polyamide and polyolefin is also insufficient.
[0022] The present invention aims to provide a polyamide resin composition, which can provide a film having excellent transparency, puncture strength and pinhole resistance without deterioration in appearance due to film gelation, and a film and a film laminate obtained using the same, and further aims to provide a pellet mixture suitable for producing the polyamide resin composition, the film and the film laminate.
[0023] Solutions for solving problems
[0024] The present invention relates to the following [1] to
[17] .
[0025] [1] A polyamide resin composition, comprising, relative to 100% by mass of the polyamide resin composition, 70 to 95% by mass of an aliphatic polyamide resin (A), 5 to 30% by mass of an ethylene / α-olefin copolymer having 3 to 8 carbon atoms having a functional group (B), and 0 to 5% by mass of other components (C), wherein in the aliphatic polyamide resin (A), the ratio of the number of methylene groups to the number of amide groups is 3 to 11, and when the number average molecular weight and weight average molecular weight of the polyamide resin composition measured by GPC are denoted as Mn and Mw, respectively, Mn is 25,000 to 46,000, and Mw / Mn is 1.5 to 3.0.
[0026] [2] The polyamide resin composition according to [1], wherein the aliphatic polyamide resin (A) is an aliphatic homopolyamide.
[0027] [3] The polyamide resin composition according to [1] or [2], wherein the aliphatic polyamide resin (A) is at least one selected from the group consisting of polyamide 4, polyamide 6, polyamide 11, polyamide 12, polyamide 46, polyamide 410, polyamide 56, polyamide 66, polyamide 510, polyamide 512, polyamide 610, polyamide 612, polyamide 1010 and polyamide 1012.
[0028] [4] The polyamide resin composition according to any one of [1] to [3], wherein the number average molecular weight Mn of the polyamide resin composition is 35,000 to 46,000.
[0029] [5] The polyamide resin composition according to any one of [1] to [4], wherein the first melting peak temperature measured based on the DSC curve when the temperature of the above-mentioned composition is increased from 0°C to 280°C at a rate of 20°C / min in an air atmosphere is in the range of 70 to 120°C, and the second melting peak temperature is in the range of 150 to 260°C.
[0030] [6] The polyamide resin composition according to any one of [1] to [5], wherein the concentration of the amino group in the composition is 2.0×10 -5 ~3.5×10 -5 eq / g, the concentration of carboxyl groups is 4.5×10 -5 ~6.0×10 -5 eq / g.
[0031] [7] The polyamide resin composition according to any one of [1] to [6], wherein the copolymer (B) is an ethylene / propylene copolymer, an ethylene / 1-butene copolymer or an ethylene / 1-hexene copolymer having a group derived from maleic anhydride.
[0032] [8] The polyamide resin composition according to any one of [1] to [7], which does not substantially contain silica.
[0033] [9] The polyamide resin composition according to any one of [1] to [8], wherein the number of gels of 50 to 99 μm in a gel measurement is 100 or less / 0.04 m for an unstretched film obtained by extruding the polyamide resin composition into a 40 μm thick unstretched film under the conditions of a barrel temperature of 190° C., 230° C. and 250° C. when the barrel region of the extruder is divided into three parts, a joint temperature of 250° C., a die temperature of 250° C., a screw speed of 25 rpm and a pulling speed of 3.0 m / min. 2 .
[0034]
[10] A polyamide film comprising the polyamide resin composition according to any one of [1] to [9].
[0035]
[11] A laminated film comprising three layers, wherein a layer comprising the polyamide resin composition according to any one of [1] to [9], an adhesive layer, and a polyolefin layer are laminated in this order.
[0036]
[12] A laminated film comprising five layers, wherein an adhesive layer and a polyolefin layer are sequentially laminated on both surfaces of a layer comprising the polyamide resin composition according to any one of [1] to [9].
[0037]
[13] The laminated film according to
[11] or
[12] , wherein the layer comprising the polyamide resin composition is a biaxially stretched layer.
[0038]
[14] The laminate film according to any one of
[11] to
[13] , which is used for food packaging.
[0039]
[15] A pellet mixture comprising a first pellet comprising a first aliphatic polyamide resin (A1) and an ethylene / α-olefin copolymer having 3 to 8 carbon atoms (B) having a functional group, and a second pellet comprising a second aliphatic polyamide resin (A2).
[0040] 100% by mass of the first pellet comprises 60 to 90% by mass of the first aliphatic polyamide resin (A1), 10 to 40% by mass of the ethylene / α-olefin copolymer having 3 to 8 carbon atoms (B) having a functional group, and 0 to 5% by mass of other components (C), wherein the MFR of the first pellet measured at 230° C. and a load of 2.16 kg according to ASTM D1238 is 1 to 40 g / 10 minutes,
[0041] The second aliphatic polyamide resin (A2) has a relative viscosity of 2.5 to 5.0 when 1 g of the polyamide resin is dissolved in 100 ml of 96% sulfuric acid according to JIS K 6920 at 25° C., a melting point of 150 to 260° C., and an MFR of 1 to 20 g / 10 minutes when measured at 230° C. and a load of 2.16 kg according to ASTM D1238.
[0042] In the aliphatic polyamide resin (A1) and the aliphatic polyamide resin (A2), the ratio of the number of methylene groups to the number of amide groups is 3 or more and 11 or less, and the melting point of the copolymer (B) is 70 to 120° C.,
[0043] The pellet mixture is melt-kneaded to form a kneaded product containing 70 to 95% by weight of the first aliphatic polyamide resin (A1) and the second aliphatic polyamide resin (A2), 5 to 30% by weight of an ethylene / α-olefin copolymer having 3 to 8 carbon atoms (B) having a functional group, and 0 to 5% by weight of other components (C).
[0044] When the number average molecular weight and the weight average molecular weight of the kneaded product measured by GPC are respectively defined as Mn and Mw, Mn is 25,000 to 46,000, and Mw / Mn is 1.5 to 3.0.
[0045]
[16] The first pellets used for mixing with the second pellets in the production of the pellet mixture described in
[15] .
[0046]
[17] The second pellets used for mixing with the first pellets in the production of the pellet mixture described in
[15] .
[0047] Effects of the Invention
[0048] According to the present invention, a polyamide resin composition can be provided, and a film and a film laminate obtained using the same, wherein the polyamide resin composition can provide a film having excellent transparency, puncture strength and pinhole resistance without deterioration of appearance caused by film gel, and can be recycled. Furthermore, a pellet mixture suitable for producing the polyamide resin composition, the film and the film laminate can be provided. DETAILED DESCRIPTION
[0049] In this specification, about the content of each component in the composition, when there are multiple substances belonging to each component in the composition, as long as there is no special record, it means the total amount of the multiple substances. In this specification, the term polyamide resin composition refers to a composition containing at least polyamide resin, including all forms of materials such as pellets, sheets, strands, chips, and molded products formed by various methods. The term pellet refers to one of the forms that the polyamide resin composition can present. Below, the polyamide resin composition and pellets described in the present invention are described in detail.
[0050] The polyamide resin composition of the present invention comprises 70 to 95% by mass of an aliphatic polyamide resin (A), 5 to 30% by mass of an ethylene / α-olefin copolymer having 3 to 8 carbon atoms (B) having a functional group, and 0 to 5% by mass of other components (C) relative to 100% by mass of the polyamide resin composition, wherein the ratio of the number of methylene groups to the number of amide groups in the aliphatic polyamide resin (A) is 3 or more and 11 or less, and when the number average molecular weight and the weight average molecular weight of the polyamide resin composition measured by GPC are defined as Mn and Mw, respectively, Mn is 25,000 to 46,000, and Mw / Mn is 1.5 to 3.0. By using the polyamide resin composition of the present invention, a film having excellent transparency, puncture strength and pinhole resistance and having no appearance deterioration due to film gel can be obtained, and material recycling of film waste can be performed.
[0051] In the present invention, material recycling refers to recycling waste as raw materials for products. Specifically, for a laminated film containing a layer comprising a polyamide resin composition, especially a laminated film containing at least a layer comprising a polyamide resin composition and a layer comprising a polyolefin, it means: after processing such as cutting and pulverizing the waste, melt-kneading it into a form such as pellets, and recycling it as a raw material for new plastic products.
[0052] [Polyamide resin composition]
[0053] <Aliphatic polyamide resin (A)>
[0054] The aliphatic polyamide resin (A) contains an aliphatic group in the structural repeating unit and has an amide bond (—CONH—) in the main chain.
[0055] Examples of the aliphatic polyamide resin (A) include aliphatic homopolyamide and aliphatic copolymer polyamide, and these may be used alone or in combination of two or more.
[0056] (Aliphatic homopolyamide)
[0057] Aliphatic homopolyamide is a polyamide resin containing one structural unit derived from an aliphatic monomer. Aliphatic homopolyamide can be formed from at least one of a lactam and an aminocarboxylic acid as a hydrolyzate of the lactam, or can be formed from a combination of a diamine and a dicarboxylic acid. Here, regarding the combination of a diamine and a dicarboxylic acid, the combination of a diamine and a dicarboxylic acid is regarded as one monomer. From the viewpoint of improving the elastic modulus, the aliphatic polyamide resin (A) is preferably an aliphatic homopolyamide.
[0058] Examples of lactams include ε-caprolactam, enantholactam, undecanolactam, laurolactam (ω-laurolactam), α-pyrrolidone, and α-piperidone. Among these, one selected from the group consisting of ε-caprolactam, undecanolactam, and laurolactam is preferred from the viewpoint of polymerization productivity.
[0059] Examples of the aminocarboxylic acid include ε-aminocaproic acid, 7-aminoheptanoic acid, 9-aminononanoic acid, 11-aminoundecanoic acid, and 12-aminododecanoic acid.
[0060] Examples of the diamine include aliphatic diamines such as ethylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, undecamethylenediamine, dodecamethylenediamine, tridecanediamine, tetradecanediamine, pentadecanediamine, hexadecanediamine, heptadecanediamine, octadecanediamine, nonadecanediamine, eicosanediamine, 2-methyl-1,8-octanediamine, and 2,2,4 / 2,4,4-trimethylhexamethylenediamine.
[0061] Examples of the dicarboxylic acid include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, octadecanedioic acid, and eicosanedioic acid.
[0062] Specific examples of the aliphatic homopolyamide include polyamide 4, polyamide 6, polyamide 7, polyamide 9, polyamide 10, polyamide 11, polyamide 12, polyamide 26, polyamide 44, polyamide 45, polyamide 46, polyamide 48, polyamide 49, polyamide 54, polyamide 55, polyamide 56, polyamide 66, polyamide 410, polyamide 412, polyamide 58, polyamide 59, polyamide 510, polyamide 512, polyamide 64, polyamide 66, 5. polyamide 68, polyamide 69, polyamide 610, polyamide 611, polyamide 612, polyamide 96, polyamide 98, polyamide 99, polyamide 105, polyamide 616, polyamide 618, polyamide 910, polyamide 912, polyamide 106, polyamide 108, polyamide 109, polyamide 1010, polyamide 1012, polyamide 125, polyamide 126, polyamide 129, polyamide 1210, polyamide 1212, polyamide 122. These aliphatic homopolyamides can be used alone or in the form of a mixture of two or more. Among these, from the viewpoint of availability, economy, mechanical properties and heat resistance of the obtained molded article, the aliphatic polyamide resin (A) is preferably at least one selected from the group consisting of polyamide 4, polyamide 6, polyamide 11, polyamide 12, polyamide 46, polyamide 410, polyamide 56, polyamide 66, polyamide 510, polyamide 512, polyamide 610, polyamide 612, polyamide 1010 and polyamide 1012, and more preferably at least one selected from the group consisting of polyamide 6 and polyamide 66.
[0063] (Aliphatic Copolyamide)
[0064] Aliphatic copolyamide is a polyamide resin containing two or more structural units derived from aliphatic monomers. The structural units of the aliphatic copolyamide are derived from monomers selected from the group consisting of a combination of a diamine and a dicarboxylic acid, a lactam, and an aminocarboxylic acid. Here, regarding the combination of a diamine and a dicarboxylic acid, a combination of one diamine and one dicarboxylic acid is regarded as one monomer.
[0065] Examples of the diamine include the same diamines as those exemplified as the raw materials of the aliphatic homopolyamide.
[0066] Examples of the dicarboxylic acid include the same dicarboxylic acids as those exemplified as the raw materials of the aliphatic homopolyamide.
[0067] Examples of the lactam include the same lactams as those exemplified as the raw material of the aliphatic homopolyamide. Examples of the aminocarboxylic acid include the same aminocarboxylic acids as those exemplified as the raw material of the aliphatic homopolyamide.
[0068] These diamines, dicarboxylic acids, lactams, and aminocarboxylic acids may be used alone or in combination of two or more.
[0069] As the aliphatic copolyamide, specifically, there can be mentioned copolymers obtained by combining two or more monomers forming the polyamides exemplified as aliphatic homopolyamides, and more specifically, there can be mentioned aliphatic copolyamides of polyamide 4 / 6, polyamide 6 / 66, polyamide 6 / 69, polyamide 6 / 610, polyamide 6 / 611, polyamide 6 / 612, polyamide 6 / 10, polyamide 6 / 11, polyamide 6 / 12, polyamide 6 / 66 / 12, polyamide 6 / 66 / 610, polyamide 6 / 66 / 612, polyamide 6 / 610 / 12 and polyamide 6 / 612 / 12. These aliphatic copolyamides can be used alone or in the form of a mixture of two or more.
[0070] The aliphatic copolymer polyamide is preferably polyamide 6 / 66, polyamide 6 / 12, polyamide 6 / 66 / 12, polyamide 6 / 610 / 12, polyamide 6 / 612 / 12, and a mixture thereof, and more preferably polyamide 6 / 12 and / or polyamide 6 / 66 / 12, and a mixture thereof.
[0071] These aliphatic copolymer polyamides preferably contain 50% by mass or more, more preferably 70% by mass or more, and even more preferably 75% by mass or more of structural units having 6 carbon atoms.
[0072] As the manufacturing apparatus of the aliphatic polyamide resin (A), there can be cited known polyamide manufacturing apparatuses such as intermittent reactors, single-tank to multi-tank continuous reaction apparatuses, tubular continuous reaction apparatuses, single-screw type mixing extruders, twin-screw type mixing extruders and other mixing reaction extruders. As the polymerization method, known methods such as melt polymerization, solution polymerization, and solid phase polymerization can be used, and polymerization can be carried out by repeatedly performing normal pressure, reduced pressure, and pressurized operations. These polymerization methods can be used alone or in appropriate combination.
[0073] (Ratio of the number of methylene groups to the number of amide groups)
[0074] In the aliphatic polyamide resin (A), the ratio of the number of methylene groups ([CH2]) to the number of amide groups ([NHCO]) [CH2] / [NHCO] (hereinafter, the ratio of the number of methylene groups to the number of amide groups may be referred to as [CH2] / [NHCO]) is 3 or more and 11 or less. By setting [CH2] / [NHCO] to the above range, the molding processability, the mechanical properties and the heat resistance of the obtained molded article can be improved. [CH2] / [NHCO] is preferably 3 or more and 9 or less, more preferably 4 to 8, and even more preferably 4 to 7.
[0075] Examples of aliphatic homopolyamides in which the ratio [CH2] / [NHCO] of the number of methylene groups to the number of amide groups is 3 or more and 11 or less include polyamide 4:3.0, polyamide 6:5.0, polyamide 7:6.0, polyamide 9:8.0, polyamide 10:9.0, polyamide 11:10.0, polyamide 12:11.0, polyamide 26:3.0, polyamide 44:3.0, polyamide 45:3.5, polyamide 46:4.0, polyamide 48:5.0, polyamide 49:5.5, polyamide 410:6.0, polyamide 412:7.0, polyamide 54:3.5, polyamide 55:4.0, polyamide 56:4.5, polyamide 58:5.5, polyamide 59:6.0, polyamide 510:6.5, polyamide 512:7.5, polyamide 64: 4.0, polyamide 65:4.5, polyamide 66:5.0, polyamide 68:6.0, polyamide 69:6.5, polyamide 610:7.0, polyamide 611:7.5, polyamide 612:8.0, polyamide 616:10.0, polyamide 618:11.0, polyamide 96:6.5, polyamide 98:7.5, polyamide 99:8.0, polyamide 910:8. 5, polyamide 912:9.5, polyamide 105:6.5, polyamide 106:7.0, polyamide 108:8.0, polyamide 109:8.5, polyamide 1010:9.0, polyamide 1012:10.0, polyamide 125:7.5, polyamide 126:8.0, polyamide 129:9.5, polyamide 1210:10.0 and polyamide 1212:11.0. In addition, as the aliphatic copolymer polyamide having a ratio [CH2] / [NHCO] of the number of methylene groups to the number of amide groups of 3 or more and 11 or less, there can be mentioned copolymers obtained using a plurality of raw material monomers for forming the above-mentioned aliphatic homopolyamide. One or more of these can be used.
[0076] When the aliphatic polyamide resin (A) is a copolymer, the ratio of the number of methylene groups to the number of amide groups [CH2] / [NHCO] can be calculated as follows: the ratio of the number of methylene groups to the number of amide groups [CH2] / [NHCO] in the homopolymer of the monomer constituting the repeating unit of the copolymer is multiplied by the molar fraction of the structural repeating unit to obtain a numerical value, and the above numerical values are added for all the structural repeating units to calculate.
[0077] When the aliphatic polyamide resin (A) is a mixture of two or more aliphatic polyamide resins, the ratio of the number of methylene groups to the number of amide groups [CH2] / [NHCO] can be calculated as follows: the ratio of the number of methylene groups to the number of amide groups [CH2] / [NHCO] in each aliphatic polyamide resin is multiplied by the mixing ratio expressed as a molar ratio to obtain a numerical value, and the above numerical values are added for all aliphatic polyamide resins to calculate.
[0078] From the viewpoint of reducing film gelation when formed into a film, improving transparency, puncture strength and pinhole resistance, the aliphatic polyamide resin (A) is preferably selected from polyamide 4, polyamide 6, polyamide 11, polyamide 12, polyamide 46, polyamide 410, polyamide 56, polyamide 66, polyamide 510, polyamide 512, polyamide 610, polyamide 612, polyamide 1010, polyamide 1012, polyamide 6 / 66, polyamide 6 / 12 and polyamide 6 / At least one selected from the group consisting of polyamide 66 / 12, more preferably at least one selected from the group consisting of polyamide 4, polyamide 6, polyamide 11, polyamide 12, polyamide 46, polyamide 410, polyamide 56, polyamide 66, polyamide 510, polyamide 512, polyamide 610, polyamide 612, polyamide 1010 and polyamide 1012, further preferably at least one selected from the group consisting of polyamide 6 and polyamide 66, and particularly preferably polyamide 6.
[0079] (Physical Properties of Aliphatic Polyamide Resin (A))
[0080] From the viewpoint of molding processability, the relative viscosity of the aliphatic polyamide resin (A) is preferably 2.0 to 5.0, more preferably 2.0 to 4.5, and even more preferably 2.1 to 3.5. By setting the relative viscosity of the aliphatic polyamide resin (A) to the above range, it is easy to ensure the moldability of the film and the mechanical strength of the obtained film.
[0081] The relative viscosity of the aliphatic polyamide resin (A) is a value measured by dissolving 1 g of the polyamide resin (A) in 100 ml of 96% sulfuric acid at 25° C. in accordance with JIS K 6920. When the aliphatic polyamide resin (A) is a combination of two or more types, the relative viscosity is preferably measured by the above method, but when the relative viscosities of the various polyamide resins and their mixing ratios are known, the values obtained by multiplying the respective relative viscosities by their mixing ratios may be added together to calculate an average value, and the average value may be used as the relative viscosity of the aliphatic polyamide resin (A).
[0082] From the viewpoint of reducing film gelation, the terminal amino group concentration of the aliphatic polyamide resin (A) is preferably 2.0×10 -5 ~5.5×10 -5 eq / g, more preferably 2.5×10 -5 ~5.0×10 -5 eq / g, more preferably 2.8×10 -5 ~4.8×10 -5 The terminal amino group concentration can be expressed as the equivalent of amino groups per 1 g of polymer, and can be measured by dissolving a polyamide resin in a phenol / methanol mixed solution and titrating with 1 / 50N hydrochloric acid.
[0083] When the aliphatic polyamide resin (A) contains two or more polyamide resin components having different terminal amino group concentrations, the terminal amino group concentration in the aforementioned polyamide resin is preferably measured by the above-mentioned neutralization titration. However, when the terminal amino group concentrations of each polyamide resin component and the mixing ratio thereof are known, the values obtained by multiplying each terminal amino group concentration by its mixing ratio can be added together to calculate the average value, and the average value can be set as the terminal amino group concentration of the aforementioned polyamide resin.
[0084] From the viewpoint of reducing film gelation, the terminal carboxyl group concentration of the aliphatic polyamide resin (A) is preferably 2.0×10 -5 ~5.5×10 -5 eq / g, more preferably 2.5×10 -5 ~5.0×10 -5 eq / g, more preferably 2.8×10 -5 ~4.8×10 -5 eq / g. The terminal carboxyl group concentration can be expressed as the equivalent of carboxyl groups per 1 g of the polymer, and can be measured by dissolving a polyamide resin in benzyl alcohol and titrating with a 1 / 20N sodium hydroxide solution.
[0085] When the aliphatic polyamide resin (A) contains two or more polyamide resin components having different terminal carboxyl group concentrations, the terminal carboxyl group concentration in the aforementioned polyamide resin is preferably measured by the above-mentioned neutralization titration, but when the terminal carboxyl group concentrations of each polyamide resin component and the mixing ratio thereof are known, the values obtained by multiplying each terminal carboxyl group concentration by its mixing ratio can be added together to calculate the average value, and the average value can be used as the terminal carboxyl group concentration of the aforementioned polyamide resin.
[0086] From the viewpoint of reducing film gelation, the concentration difference between the terminal carboxyl group and the terminal amino group of the aliphatic polyamide resin (A) is preferably -3.0×10 -5 ~3.0×10 -5 eq / g, more preferably -2.0×10 -5 ~2.0×10 -5 eq / g, more preferably -1.0×10 -5 ~1.0×10 -5 eq / g.
[0087] From the viewpoint of mechanical properties, it is preferred that the number average molecular weight Mn of the aliphatic polyamide resin (A) measured based on GPC is 25,000 to 65,000, and the ratio of the weight average molecular weight Mw to Mn: Mw / Mn is 1.0 to 4.0. The number average molecular weight Mn is more preferably 30,000 to 65,000, further preferably 33,000 to 63,000, and further preferably 35,000 to 60,000. The number average molecular weight Mn may also be 25,000 to 60,000. In addition, Mw / Mn is more preferably 1.0 to 3.0, and further preferably 1.0 to 2.5. The values of Mn and Mw are measured values based on gel permeation chromatography (GPC).
[0088] From the viewpoint of molding processability, the melting point of the aliphatic polyamide resin (A) is preferably 150 to 260° C., more preferably 160 to 250° C., and still more preferably 180 to 240° C. The melting point refers to the melting peak temperature in a DSC curve when the aliphatic polyamide resin (A) is heated to 280° C. in an air atmosphere, maintained at this temperature for 5 minutes, then the temperature is lowered to 0° C. at a cooling rate of 20° C. / min, and then the temperature is raised from 0° C. to 280° C. at a rate of 20° C. / min.
[0089] From the viewpoint of molding processability, the melt flow rate (MFR) of the aliphatic polyamide resin (A) measured at 230°C and a load of 2.16 kg in accordance with ASTM D1238 is preferably 1 to 100 g / 10 min, more preferably 2 to 90 g / 10 min, further preferably 3 to 80 g / 10 min.
[0090] (Content of Aliphatic Polyamide Resin (A))
[0091] The content of aliphatic polyamide resin (A) is 70 to 95% by mass in 100% by mass of the polyamide resin composition. By setting the content of aliphatic polyamide resin (A) to the above range, aliphatic polyamide resin (A) and ethylene / α-olefin copolymer (B) having a functional group and having 3 to 8 carbon atoms show good compatibility, and the melt stability of the polyamide resin composition and the moldability of the film are improved. Furthermore, the appearance deterioration caused by the film gel of the polyamide film molded from the polyamide resin composition can be suppressed, and the transparency and good pinhole resistance of the film can be maintained. Furthermore, the material recyclability of the waste of the film is also improved. The content of aliphatic polyamide resin (A) is preferably 75 to 95% by mass, more preferably 80 to 90% by mass in 100% by mass of the polyamide resin composition.
[0092] <Ethylene / α-olefin copolymer having 3 to 8 carbon atoms (B) having a functional group (hereinafter also referred to as copolymer (B))>
[0093] The polyamide resin composition comprises an ethylene / α-olefin copolymer (B) having a functional group and having 3 to 8 carbon atoms. By containing the copolymer (B), the pinhole resistance of the film formed from the polyamide resin composition in a low temperature environment can be improved. In addition, the copolymer (B) functions as a compatibilizer for polyamide and polyolefin by having a functional group. Therefore, for a laminated film comprising at least a layer comprising a polyamide resin composition and a layer comprising a polyolefin, when the waste of the film is recycled, the compatibility of the two layers is improved, and the homogeneity of the recycled plastic raw material is improved. The copolymer (B) can be a combination of one or more.
[0094] As the functional group of the copolymer (B), carboxyl group (optionally forming a salt), anhydride group, carboxylate group, carboxylic acid imide group, carboxylic acid amide group, epoxy group, etc. can be listed. It can be considered that the amino group of the aliphatic polyamide resin (A) reacts with at least a part of these functional groups. Among them, from the viewpoint of compatibility of polyamide and polyolefin, it is preferably at least one selected from the group consisting of carboxyl group, carboxylate group and anhydride group, and more preferably anhydride group.
[0095] As methods for introducing functional groups into ethylene / α-olefin copolymers having 3 to 8 carbon atoms, there are listed: (i) a method of copolymerizing a copolymerizable monomer having a functional group during the polymerization of the copolymer; (ii) a method of introducing a functional group into the molecular chain or molecular terminal of the ethylene / α-olefin copolymer having 3 to 8 carbon atoms using a polymerization initiator, a chain transfer agent, etc.; (iii) a method of grafting a compound having the above-mentioned functional group and a graftable functional group onto the ethylene / α-olefin copolymer having 3 to 8 carbon atoms, etc. These introduction methods can be used alone or in appropriate combination. Among them, from the viewpoint of suppressing the deterioration of the appearance caused by the film gel of the film molded from the polyamide resin composition and maintaining the transparency and good pinhole resistance of the film, the copolymer (B) is preferably produced by the method (ii) or (iii).
[0096] Examples of copolymerizable monomers having functional groups, compounds having the aforementioned functional groups and graftable functional groups, etc. include acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, crotonic acid, mesaconic acid, citraconic acid, glutaconic acid, cis-4-cyclohexene-1,2-dicarboxylic acid, endo-bicyclo-[2.2.1]-5-heptene-2,3-dicarboxylic acid and metal salts of these carboxylic acids, monomethyl maleate, monomethyl itaconate, methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, hydroxyethyl acrylate, methacrylic acid, The present invention relates to methyl methacrylate, 2-ethylhexyl methacrylate, hydroxyethyl methacrylate, aminoethyl methacrylate, dimethyl maleate, dimethyl itaconate, maleic anhydride, itaconic anhydride, citraconic anhydride, endo-bicyclo-[2.2.1]-5-heptene-2,3-dicarboxylic anhydride, maleimide, N-ethylmaleimide, N-butylmaleimide, N-phenylmaleimide, acrylamide, methacrylamide, glycidyl acrylate, glycidyl methacrylate, glycidyl ethacrylate, glycidyl itaconate, glycidyl citraconic acid, etc. They can be used alone or in combination of two or more. Among these, maleic anhydride, itaconic anhydride or citraconic anhydride are preferred, maleic anhydride or itaconic anhydride are further preferred, and maleic anhydride is particularly preferred.
[0097] From the viewpoint of compatibility between polyamide and polyolefin and reduction of film gelation, the functional group concentration in the copolymer (B) is preferably 1.0×10 -5 ~60×10 -5 eq / g, more preferably 2.0×10 -5 ~40×10 -5 eq / g, more preferably 3.0×10 -5 ~30×10 -5 Regarding the functional group concentration of the copolymer (B), when the functional group is a carboxyl group, anhydride group or carboxylate group, it can be expressed as the carboxyl group equivalent per 1g of the polymer, and is measured by neutralization titration based on a 0.1 equivalent KOH ethanol solution using a sample solution prepared using a solvent such as xylene and phenolphthalein as an indicator.
[0098] When the copolymer (B) is a copolymer having a group derived from maleic anhydride obtained by the above method (ii) or (iii), the maleic anhydride modification rate (content (mass %) of the group derived from maleic anhydride) is preferably 0.1% to 3% by mass, more preferably 0.3% to 2% by mass, and particularly preferably 0.5% to 1.5% by mass. By setting the maleic anhydride modification rate to the above range, the compatibility of polyamide and polyolefin can be improved, and the film gel can be reduced. As a method for determining the maleic anhydride modification rate, there can be listed: a method of converting the carboxyl equivalent obtained by the above neutralization titration into a maleic acid modification rate; by using FT-IR and according to the wave number 1780cm-1 attributed to the carbonyl group -1 A method of measuring by separately preparing a standard curve based on the peak intensity.
[0099] The copolymer (B) is an ethylene / α-olefin copolymer having 3 to 8 carbon atoms. From the viewpoint of suppressing the deterioration of the appearance of a film formed from the polyamide resin composition due to film gelation and maintaining the transparency and good pinhole resistance of the film, the copolymer (B) preferably does not contain a copolymerizable monomer having a functional group as a copolymerization component.
[0100] The number of carbon atoms of the α-olefin is 3 to 8, preferably 3 to 7, and more preferably 4 to 6. Specific examples of α-olefins having 3 to 8 carbon atoms include 1-propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl-1-hexene, 3-ethyl-1-hexene, etc. They can be used alone or in combination of two or more. Among them, from the viewpoint of molding processability, 1-propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene and 1-octene are preferred, 1-propylene, 1-butene and 1-hexene are more preferred, and 1-hexene is particularly preferred.
[0101] From the viewpoint of compatibility between polyamide and polyolefin, in the copolymer (B), the proportion of the α-olefin monomer having 3 to 8 carbon atoms in the total 100 mol% of the ethylene monomer and the α-olefin monomer having 3 to 8 carbon atoms constituting the copolymer is preferably 1 to 99 mol%, more preferably 5 to 95 mol%, and even more preferably 10 to 90 mol%.
[0102] The molecular structure of the copolymer (B) may be a straight chain or a branched chain having a long chain side chain or a short chain side chain. The copolymer (B) may be copolymerized with 1,4-pentadiene, 1,4-hexadiene, 1,5-hexadiene, 1,4-octadiene, 1,5-octadiene, 1,6-octadiene, 1,7-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, 7-methyl-1,6-octadiene, 4-ethylidene-8-methyl-1,7-nonadiene, 4,8-dimethyl-1,4,8-decatriene (DM The polyenes include non-conjugated dienes such as 2-nitropropene, ...
[0103] Among them, from the viewpoint of compatibility between polyamide and polyolefin, copolymer (B) is preferably an ethylene / α-olefin copolymer having a group derived from at least one acid anhydride selected from the group consisting of maleic anhydride and itaconic anhydride, more preferably an ethylene / propylene copolymer, an ethylene / 1-butene copolymer, an ethylene / 1-hexene copolymer or an ethylene / 1-octene copolymer having a group derived from maleic anhydride, further preferably an ethylene / propylene copolymer, an ethylene / 1-butene copolymer or an ethylene / 1-hexene copolymer having a group derived from maleic anhydride, still more preferably an ethylene / 1-butene copolymer or an ethylene / 1-hexene copolymer having a group derived from maleic anhydride, and particularly preferably an ethylene / 1-hexene copolymer having a group derived from maleic anhydride.
[0104] From the viewpoint of molding processability, the melting point of the copolymer (B) is preferably 70 to 120° C., more preferably 75 to 120° C., and further preferably 80 to 115° C. The melting point refers to the melting peak temperature in a DSC curve when the copolymer (B) is heated to 280° C. in an air atmosphere, maintained at this temperature for 5 minutes, then the temperature is lowered to 0° C. at a cooling rate of 20° C. / min, and then the temperature is raised from 0° C. to 280° C. at a rate of 20° C. / min.
[0105] From the viewpoint of reducing film gelation, the melt flow rate (MFR) of the copolymer (B) measured at 230°C and a load of 2.16 kg in accordance with ASTM D1238 is preferably 1 to 100 g / 10 min, more preferably 3 to 90 g / 10 min, and even more preferably 5 to 70 g / 10 min.
[0106] (Content of copolymer (B))
[0107] The content of copolymer (B) is 5 to 30% by mass in 100% by mass of the polyamide resin composition. By setting the content of copolymer (B) to the above range, aliphatic polyamide resin (A) and copolymer (B) show good compatibility, and the melt stability and film formability of the polyamide resin composition are improved. Furthermore, the appearance deterioration caused by the film gel of the polyamide film molded from the polyamide resin composition can be suppressed, the transparency of the film can be maintained, and the pinhole resistance under low temperature environment can be improved. Furthermore, for a laminated film containing at least a layer containing a polyamide resin composition and a layer containing a polyolefin, when the waste of the film is recycled, the compatibility of the two layers is improved, and the homogeneity of the recycled plastic raw material is improved. The content of copolymer (B) is preferably 5 to 25% by mass, more preferably 5 to 20% by mass, and further preferably 7 to 15% by mass in 100% by mass of the polyamide resin composition. The content of copolymer (B) can also be 10 to 20% by mass.
[0108] If the content of the copolymer (B) in 100% by mass of the polyamide resin composition is less than 5% by mass, the pinhole resistance of the molded film in a low temperature environment will not be improved, and the material recyclability will also be deteriorated. If the above content exceeds 30% by mass, the dispersibility of the copolymer (B) in the polyamide resin composition will deteriorate, the gel of the film will increase, and the appearance of the film will deteriorate.
[0109] <Other ingredients (C)>
[0110] The polyamide resin composition may contain other components (C) in addition to the components (A) and (B). Examples of other components include polyamide resins other than the component (A), for example, polyamide resins having alicyclic groups or aromatic groups in the main chain or side chain; thermoplastic resins other than the component (B); antioxidants, anti-blocking agents, lubricants, nucleating agents, plasticizers, foaming agents, stabilizers, ultraviolet absorbers, weathering agents, anti-fogging agents, colorants, etc. Among them, the polyamide resin composition preferably contains an antioxidant and / or a lubricant.
[0111] Even if the polyamide resin composition does not contain an anti-blocking agent, anti-blocking properties suitable for a film can be obtained. From the viewpoints of economy and transparency, the polyamide resin composition preferably does not contain substantially an anti-blocking agent, and from the viewpoint of transparency, it is more preferably not containing substantially silica.
[0112] Here, “substantially free of” means that the content ratio of the anti-blocking agent or silica in 100% by mass of the polyamide resin composition is less than 0.01% by mass, preferably less than 0.005% by mass, and more preferably less than 0.001% by mass.
[0113] From the viewpoint of further improving the handling property of the film formed, the polyamide resin composition may contain an anti-blocking agent. As the anti-blocking agent, minerals such as diatomaceous earth, calcium carbonate, feldspar, quartz, synthetic silica, cross-linked resin beads, etc. can be listed. The anti-blocking agent can be a combination of one or more.
[0114] From the viewpoint of further reducing the amount of film gel, the polyamide resin composition preferably contains an antioxidant. Examples of the antioxidant include organic antioxidants such as phenolic compounds, phosphorus compounds, and sulfur compounds; inorganic antioxidants such as halogenated metal compounds, and the like. The antioxidant may be one or a combination of two or more.
[0115] From the viewpoints of improving the smoothness of the pellets before molding, improving the smoothness of the processing machine and the pellets, and improving the smoothness of the films molded, the polyamide resin composition preferably includes a lubricant. As lubricants, compounds such as terminal modified products of polyalkylene glycol, phosphates or phosphites, higher fatty acid monoesters, higher fatty acids or their metal salts, carboxylic acid amides, low molecular weight polyethylene, magnesium silicate, and substituted benzylidene sorbitols can be listed. They can be a combination of one or more.
[0116] The content of other component (C) is 0 to 5 mass %, more preferably 0 to 3 mass %, further preferably 0 to 2 mass %, further preferably 0 to 1 mass %, particularly preferably 0.1 to 1 mass % in 100 mass % of the polyamide resin composition.
[0117] [Physical properties of polyamide resin composition]
[0118] The number average molecular weight Mn of the polyamide resin composition measured by GPC is 25,000 to 46,000, and the ratio of the weight average molecular weight Mw to Mn: Mw / Mn is 1.5 to 3.0. The present inventors have found that by setting the Mn and Mw / Mn of the polyamide resin composition to the above range, the formation of film gel of the polyamide film molded from the polyamide resin composition can be significantly suppressed. The number average molecular weight Mn is more preferably 35,000 to 46,000, further preferably 36,000 to 45,500, and further preferably 37,000 to 44,000. In addition, Mw / Mn is more preferably 1.5 to 2.8, and further preferably 1.6 to 2.5. The values of Mn and Mw are measured values obtained by gel permeation chromatography (GPC).
[0119] Regarding the polyamide resin composition, the first melting peak temperature measured by the DSC curve when the composition is heated to 280°C in an air atmosphere, maintained at this temperature for 5 minutes, then reduced to 0°C at a cooling rate of 20°C / min, and then heated from 0°C to 280°C at a rate of 20°C / min is preferably in the range of 70 to 120°C, and the second melting peak temperature is preferably in the range of 150 to 260°C. By having such a melting peak, the strength of the molded body can be improved. The first melting peak temperature corresponds to the melting point of the copolymer (B), preferably in the range of 74 to 120°C, and more preferably in the range of 78 to 113°C. In addition, the second melting peak temperature corresponds to the melting point of the aliphatic polyamide resin (A), preferably in the range of 160 to 250°C, and more preferably in the range of 180 to 240°C.
[0120] The amino group concentration in the polyamide resin composition is preferably 2.0×10 -5 ~3.5×10 -5 eq / g, more preferably 2.0×10 -5 ~3.4×10 -5 eq / g, more preferably 2.2×10 -5 ~3.2×10 -5 By setting the amino group concentration within the above range, film gelation can be reduced. The amino group concentration can be expressed as amino group equivalent per 1 g of the composition, and can be measured by dissolving the composition in a phenol / methanol mixed solution and titrating with 1 / 50N hydrochloric acid.
[0121] The carboxyl group concentration in the polyamide resin composition is preferably 4.5×10 -5 ~6.0×10 -5 eq / g, more preferably 4.5×10 -5 ~5.8×10 -5 eq / g, more preferably 4.6×10 -5 ~5.6×10 -5 By setting the carboxyl concentration within the above range, compatibility with polyolefins can be improved, and material recyclability can be improved. The carboxyl concentration can be expressed as carboxyl equivalent per 1 g of the composition, and can be measured by dissolving the composition in benzyl alcohol and titrating with a 1 / 20N sodium hydroxide solution.
[0122] The concentration difference between the carboxyl group and the amino group in the polyamide resin composition is preferably 1.0×10 -5 ~4.0×10 -5 eq / g, more preferably 1.0×10 -5 ~3.5×10 -5 eq / g, more preferably 1.2×10 -5~3.0×10 -5 In addition, the concentration difference between the carboxyl group and the amino group in the polyamide resin composition can also be set to 1.1×10 -5 ~3.8×10 -5 eq / g or 1.4×10 -5 ~3.4×10 -5 By setting the concentration difference between the carboxyl group and the amino group to be within the above range, it is possible to reduce film gelation and improve compatibility with polyolefins.
[0123] From the viewpoint of suppressing deterioration of the appearance caused by film gelation, for an unstretched film obtained by extruding a polyamide resin composition into a 40 μm thick film under the conditions of a barrel temperature of 190° C., 230° C. and 250° C. when the barrel region of the extruder is divided into three parts, a joint temperature of 250° C., a die temperature of 250° C., a screw speed of 25 rpm and a take-up speed of 3.0 m / min, the number of gels of 50 to 99 μm in the gel measurement is preferably 100 or less / 0.04 m 2 , preferably less than 80 / 0.04m 2 , more preferably less than 70 / 0.04m 2 The gel measurement can be performed using, for example, a fisheye counter (manufactured by FUTEC).
[0124] [Method for producing polyamide resin composition]
[0125] The method for producing the polyamide resin composition is not particularly limited. As the method for producing the polyamide resin composition, for example, the following production methods 1 and 2 can be applied.
[0126] (Manufacturing method 1)
[0127] The polyamide resin composition is obtained by melt-mixing an aliphatic polyamide resin (A) and a copolymer (B) using a mixing machine. The polyamide resin composition may contain other components (C). As mixing machines, single-screw extruders, twin-screw extruders, Banbury mixers, kneaders, open rolls, etc. can be listed. For example, any of the following methods can be used: a method of melt-mixing after mixing all raw materials using a twin-screw extruder; or a method of mixing the remaining raw materials using a side feeder during melt-mixing after mixing a portion of the raw materials. When a film is melted and molded using a film forming machine, the polyamide resin composition is preferably pre-processed into a pellet shape from the viewpoint of the manufacturing stability of the film and the dispersibility of the components in the polyamide resin composition.
[0128] (Manufacturing method 2)
[0129] The first aliphatic polyamide resin (A1) and the copolymer (B) are melt-kneaded in advance using a kneading machine to obtain a melt-kneaded product (D). A second aliphatic polyamide resin (A2) is prepared separately. Other components (C) may be blended into the melt-kneaded product (D) and the second aliphatic polyamide resin (A2), respectively.
[0130] The melt-kneaded product (D) and the second aliphatic polyamide resin (A2) can be respectively formed into pellets, and then these pellets and other components (C) as required can be uniformly dry-mixed in a specific ratio using, for example, a drum, a stirrer, etc. to obtain a pellet mixture. These pellet mixtures can also be melt-kneaded using a mixing mill to obtain a polyamide resin composition. As the mixing mill, the mixing mill illustrated in the manufacturing method 1 can be used.
[0131] Wherein, preferably by utilizing single screw extruder this pellet mixture is melt-mixed to manufacture polyamide resin composition.By using multipolymer (B) and the first aliphatic polyamide resin (A1) are melt-mixed in advance to manufacture melt-mixed product (D) and after being processed into pellets, the pellet mixture obtained by dry blending it with the pellets of the second aliphatic polyamide resin (A2), thereby the dispersibility of the multipolymer (B) in the polyamide resin composition obtained by melt-mixing is improved.It can be considered that the improvement of the dispersibility of multipolymer (B) helps to improve the formability of film, improve the pinhole resistance of film under low temperature environment and reduce film gel.
[0132] In the aliphatic polyamide resin (A1) and the aliphatic polyamide resin (A2), the ratio of the number of methylene groups to the number of amide groups is 3 or more and 11 or less. The first aliphatic polyamide resin (A1) and the second aliphatic polyamide resin (A2) can use the polyamide resins described in the aforementioned aliphatic polyamide resin (A). The first aliphatic polyamide resin (A1) and the second aliphatic polyamide resin (A2) can be the same or different. The first aliphatic polyamide resin (A1) and the second aliphatic polyamide resin (A2) are preferably aliphatic homopolyamides. The first aliphatic polyamide resin (A1) and the second aliphatic polyamide resin (A2) are preferably selected from the group consisting of polyamide 4, polyamide 6, polyamide 7, polyamide 9, polyamide 10, polyamide 11, polyamide 12, polyamide 26, polyamide 44, polyamide 45, polyamide 46, polyamide 48, polyamide 49, polyamide 410, polyamide 412, polyamide 54, polyamide 55, polyamide 56, polyamide 58, polyamide 59, polyamide 66, Polyamide 510, polyamide 512, polyamide 64, polyamide 65, polyamide 68, polyamide 69, polyamide 610, polyamide 611, polyamide 612, polyamide 96, polyamide 98, polyamide 99, polyamide 105, polyamide 616, polyamide 618, polyamide 910, polyamide 912, polyamide 106, polyamide 108, polyamide 109, polyamide 1010, polyamide 1012, polyamide 125, polyamide 126, Polyamide 129, polyamide 1210, polyamide 1212, polyamide 122, polyamide 4 / 6, polyamide 6 / 66, polyamide 6 / 69, polyamide 6 / 610, polyamide 6 / 611, polyamide 6 / 612, polyamide 6 / 10, polyamide 6 / 11, polyamide 6 / 12, polyamide 6 / 66 / 12, polyamide 6 / 66 / 610, polyamide 6 / 66 / 612, polyamide 6 / 610 / 12 and polyamide 6 / 612 / 12 group It is more preferred to use at least one selected from the group consisting of polyamide 4, polyamide 6, polyamide 11, polyamide 12, polyamide 46, polyamide 410, polyamide 56, polyamide 66, polyamide 510, polyamide 512, polyamide 610, polyamide 612, polyamide 1010 and polyamide 1012. It is further preferred to use at least one selected from the group consisting of polyamide 6 and polyamide 66, and polyamide 6 is particularly preferred. In addition, polyamide 6 / 66 may be used as the first aliphatic polyamide resin (A1) and the second aliphatic polyamide resin (A2). The first aliphatic polyamide resin (A1) and the second aliphatic polyamide resin (A2) may be one or a combination of two or more.
[0133] [Pellet mixture]
[0134] When the polyamide resin composition is manufactured by the above-mentioned manufacturing method 2, it is preferred to use a pellet mixture comprising a first pellet and a second pellet, wherein the first pellet comprises a first aliphatic polyamide resin (A1) and an ethylene / α-olefin copolymer (B) having a functional group and having 3 to 8 carbon atoms (hereinafter also referred to as copolymer (B)), and the second pellet comprises a second aliphatic polyamide resin (A2). It should be noted that the second pellet is not the first pellet. That is, the polyamide resin compositions constituting the first pellet and the second pellet are different from each other. Regarding the second pellet, in 100% by mass of the second pellet, less than 1.0% by mass of the copolymer (B) may be included, preferably without the copolymer (B). The first pellet and the second pellet may be a combination of one or more of them.
[0135] The first pellets and the second pellets may each contain other components (C) such as an antioxidant and a lubricant. In addition, the pellet mixture may contain other components (C) such as an antioxidant and a lubricant in addition to the first pellets and the second pellets.
[0136] The first aliphatic polyamide resin (A1) and the second aliphatic polyamide resin (A2) may be the same as or different from the polyamide resin described above for the aliphatic polyamide resin (A).
[0137] (First pellet)
[0138] From the viewpoint of melt stability during melt kneading when manufacturing the first pellet, the content of the first aliphatic polyamide resin (A1) is preferably 60 to 90% by mass in 100% by mass of the first pellet. From the viewpoint of reducing film gel, the content of the first aliphatic polyamide resin (A1) is more preferably 65% by mass or more, and further preferably 70% by mass or more in 100% by mass of the first pellet. In addition, from the viewpoint of improving mechanical properties, the content of the first aliphatic polyamide resin (A1) is more preferably 88% by mass or less, further preferably 85% by mass or less, and particularly preferably 80% by mass or less in 100% by mass of the first pellet.
[0139] Regarding the copolymer (B), including the preferred embodiment, it is as described above. From the viewpoint of molding processability, the melting point of the copolymer (B) is preferably 70 to 120°C, more preferably 75 to 120°C, and further preferably 80 to 115°C. The melting point refers to the melting peak temperature in the DSC curve when the copolymer (B) is heated to 280°C in an air atmosphere, maintained at this temperature for 5 minutes, then the temperature is lowered to 0°C at a cooling rate of 20°C / min, and then the temperature is raised from 0°C to 280°C at a rate of 20°C / min.
[0140] From the viewpoint of pinhole resistance and material recycling of film waste, the content of copolymer (B) is preferably 10 to 40% by mass in 100% by mass of the first pellet. From the viewpoint of pinhole resistance and material recycling of film waste, the content of copolymer (B) is more preferably 12% by mass or more, further preferably 15% by mass or more, and particularly preferably 20% by mass or more. In addition, from the viewpoint of film transparency and film gel, the content of copolymer (B) is more preferably 35% by mass or less, further preferably 32% by mass or less in 100% by mass of the first pellet. The content of copolymer (B) can also be set to 30% by mass or less in 100% by mass of the first pellet.
[0141] From the viewpoint of molding processability, the content of other components (C) is preferably 0 to 5% by mass in 100% by mass of the first pellet. The content of other components (C) is more preferably 3% by mass or less, and further preferably 1% by mass or less. In addition, the content of other components (C) is more preferably 0.1% by mass or more, and further preferably 0.2% by mass or more in 100% by mass of the first pellet.
[0142] From the viewpoint of film formability, the MFR of the first pellet measured at 230°C and a load of 2.16 kg according to ASTM D1238 is preferably 1 to 40 g / 10 minutes. The MFR of the first pellet is more preferably 2 g / 10 minutes or more, further preferably 3 g / 10 minutes or more, and particularly preferably 4 g / 10 minutes or more. In addition, the MFR of the first pellet is more preferably 35 g / 10 minutes or less, further preferably 30 g / 10 minutes or less.
[0143] From the viewpoint of the pinhole resistance of the formed polyamide film under low temperature environment, the content of the first pellet is preferably 10% by mass or more, more preferably 15% by mass or more, and further preferably 20% by mass or more in 100% by mass of the pellet mixture. In addition, from the viewpoint of the dispersibility of each component in the polyamide resin composition, the content of the first pellet is preferably 97% by mass or less, more preferably 90% by mass or less, further preferably 80% by mass or less, and particularly preferably 70% by mass or less in 100% by mass of the pellet mixture.
[0144] (Second pellet)
[0145] The second pellets contain the second aliphatic polyamide resin (A2). The content of the second aliphatic polyamide resin (A2) is preferably 95 to 100% by mass, more preferably 97 to 100% by mass, and even more preferably 99 to 100% by mass in 100% by mass of the second pellets.
[0146] The second pellets may contain less than 1.0% by mass of the copolymer (B) in 100% by mass of the second pellets. As a preferred embodiment, the second pellets do not contain the copolymer (B).
[0147] From the viewpoint of molding processability, the content of the other component (C) is preferably 5% by mass or less, more preferably 0 to 3% by mass, and further preferably 0 to 1% by mass in 100% by mass of the second pellets. The second pellets preferably contain an antioxidant and / or a lubricant as the other component (C).
[0148] The second aliphatic polyamide resin (A2) preferably has a relative viscosity of 2.5 to 5.0 when 1 g of the polyamide resin is dissolved in 100 ml of 96% sulfuric acid at 25° C. according to JIS K 6920. By setting the relative viscosity of the second aliphatic polyamide resin (A2) to the above range, film forming processability can be improved. The relative viscosity of the second aliphatic polyamide resin (A2) is more preferably 2.8 or more, and further preferably 2.9 or more. The relative viscosity of the second aliphatic polyamide resin (A2) is more preferably 4.5 or less, and further preferably 4.1 or less.
[0149] When the second aliphatic polyamide resin (A2) is a combination of two or more types, the relative viscosity is preferably measured by the above method. When the relative viscosities of the various polyamide resins and their mixing ratios are known, the values obtained by multiplying the respective relative viscosities by their mixing ratios can be added together to calculate an average value, which is then set as the relative viscosity of the second aliphatic polyamide resin (A2).
[0150] From the viewpoint of molding processability, the melting point of the second aliphatic polyamide resin (A2) is preferably 150 to 260° C., more preferably 160 to 250° C., and further preferably 180 to 240° C. The melting point refers to the melting peak temperature in a DSC curve when the second aliphatic polyamide resin (A2) is heated to 280° C. in an air atmosphere, maintained at this temperature for 5 minutes, then the temperature is lowered to 0° C. at a cooling rate of 20° C. / min, and then the temperature is raised from 0° C. to 280° C. at a rate of 20° C. / min.
[0151] From the viewpoint of film molding processability, the MFR of the second aliphatic polyamide resin (A2) measured at 230°C and a load of 2.16 kg in accordance with ASTM D1238 is preferably 1 to 20 g / 10 min, more preferably 1 to 18 g / 10 min, further preferably 2 to 15 g / 10 min.
[0152] From the viewpoint of reducing film gelation, the terminal amino group concentration of the second aliphatic polyamide resin (A2) is preferably 2.0×10 -5 ~5.5×10 -5eq / g, more preferably 2.5×10 -5 ~5.0×10 -5 eq / g, more preferably 2.8×10 -5 ~4.8×10 -5 The method for measuring the terminal amino group concentration is the same as that described in the aliphatic polyamide resin (A).
[0153] From the viewpoint of reducing film gelation, the terminal carboxyl group concentration of the second aliphatic polyamide resin (A2) is preferably 2.0×10 -5 ~5.5×10 -5 eq / g, more preferably 2.5×10 -5 ~5.0×10 -5 eq / g, more preferably 2.8×10 -5 ~4.8×10 -5 The method for measuring the terminal carboxyl group concentration is the same as that described in the aliphatic polyamide resin (A).
[0154] From the viewpoint of reducing film gelation, the concentration difference between the terminal carboxyl group and the terminal amino group of the second aliphatic polyamide resin (A2) is preferably -3.0×10 -5 ~3.0×10 -5 eq / g, more preferably -2.0×10 -5 ~2.0×10 -5 eq / g, more preferably -1.0×10 -5 ~1.0×10 -5 eq / g.
[0155] From the viewpoint of improving mechanical properties, the number average molecular weight Mn of the second aliphatic polyamide resin (A2) measured by GPC is preferably 25,000 to 65,000, and the ratio of the weight average molecular weight Mw to Mn: Mw / Mn is preferably 1.0 to 4.0. The number average molecular weight Mn is more preferably 30,000 to 65,000, further preferably 33,000 to 63,000, and further preferably 35,000 to 60,000. The number average molecular weight Mn may also be 25,000 to 60,000. In addition, Mw / Mn is more preferably 1.0 to 3.0, and further preferably 1.0 to 2.5. The values of Mn and Mw are measured values obtained by gel permeation chromatography (GPC).
[0156] From the viewpoint of film transparency, the content of the second pellet is preferably 3% by mass or more, more preferably 10% by mass or more, further preferably 20% by mass or more, and particularly preferably 30% by mass or more in 100% by mass of the pellet mixture. In addition, from the viewpoint of pinhole resistance, the content of the second pellet is preferably 90% by mass or less, more preferably 85% by mass or less, and further preferably 80% by mass or less in 100% by mass of the pellet mixture.
[0157] (granular mixture)
[0158] The total content of the first aliphatic polyamide resin (A1) and the second aliphatic polyamide resin (A2) is preferably 70 to 95% by mass, more preferably 75 to 95% by mass, and further preferably 80 to 90% by mass in 100% by mass of the mixture after melt-kneading the pellet mixture. By setting the total content of the first aliphatic polyamide resin (A1) and the second aliphatic polyamide resin (A2) to the above range, the aliphatic polyamide resin (A) and the copolymer (B) show good compatibility, and the melt stability of the polyamide resin composition and the moldability of the film are improved. Furthermore, the appearance deterioration caused by the film gel of the polyamide film molded by the polyamide resin composition can be suppressed, and the transparency and good pinhole resistance of the film can be maintained. Furthermore, the material recyclability of the waste of the film will also be improved.
[0159] The content of copolymer (B) is preferably 5 to 30% by mass, more preferably 5 to 25% by mass, further preferably 5 to 20% by mass, and particularly preferably 10 to 20% by mass in 100% by mass of the mixture after melt kneading the pellet mixture. By setting the content of copolymer (B) to the above range, aliphatic polyamide resin (A) and copolymer (B) show good compatibility, and the melt stability and film formability of the polyamide resin composition are improved. Furthermore, the appearance deterioration caused by the film gel of the polyamide film molded by the polyamide resin composition can be suppressed, the transparency of the film can be maintained, and the pinhole resistance under low temperature environment can be improved. Furthermore, for a laminated film containing at least a layer containing a polyamide resin composition and a layer containing a polyolefin, when the waste of the film is recycled, the compatibility of the two layers is improved, and the homogeneity of the recycled plastic raw material is improved.
[0160] From the viewpoint of molding processability, the content of other component (C) is preferably 0 to 5 mass %, more preferably 0 to 3 mass %, further preferably 0 to 2 mass %, further preferably 0 to 1 mass %, particularly preferably 0.1 to 1 mass %, in 100 mass % of the kneaded product after melt-kneading the pellet mixture.
[0161] From the viewpoint of reducing film gel, the number average molecular weight Mn of the kneaded product obtained by melt-kneading the pellet mixture is 25,000 to 46,000, and the ratio of the weight average molecular weight Mw to Mn: Mw / Mn is 1.5 to 3.0. The number average molecular weight Mn is more preferably 35,000 to 46,000, further preferably 36,000 to 45,500, and further preferably 37,000 to 44,000. In addition, Mw / Mn is more preferably 1.5 to 2.8, and further preferably 1.6 to 2.5. The values of Mn and Mw are measured values obtained by gel permeation chromatography (GPC).
[0162] The polyamide resin composition can be obtained by melt-kneading the pellet mixture. The preferred ranges of the first melting peak temperature, the second melting peak temperature, the amino group concentration, the carboxyl group concentration, the difference in concentration between the carboxyl group and the amino group, the MFR measured at 230° C. and a load of 2.16 kg according to ASTM D1238, and the gel number of the unstretched film obtained by extrusion molding of the polyamide resin composition thus obtained are as described above.
[0163] Another aspect of the present invention is the first pellets, which are used to be mixed with the second pellets in the production of a pellet mixture. Still another aspect of the present invention is the second pellets, which are used to be mixed with the first pellets in the production of a pellet mixture.
[0164] (Manufacturing of pellets)
[0165] The pellets can be obtained by, for example, extruding the polyamide resin composition from an extruder or the like into a strand shape and cutting the strand with a cutter having a rotating blade.
[0166] The shape of the pellets includes spherical, elongated, spheroidal, slightly deformed shapes of precise spheroidal, and cylindrical shapes with circular or elliptical cross sections. Among them, spherical, spheroidal, and cylindrical shapes with circular or elliptical cross sections are preferred.
[0167] When the cross section of the pellet is an ellipse, the major diameter is preferably 1 to 5 mm, more preferably 2 to 4 mm, and further preferably 2.0 to 3.5 mm. In addition, when the cross section of the pellet is an ellipse, the minor diameter is preferably 1 to 3 mm, more preferably 2 to 3 mm. The ratio of the major diameter to the minor diameter (major diameter / minor diameter) is not particularly limited, but is preferably 1 to 4.
[0168] The major and minor diameters of the pellets can be controlled by, for example, adjusting the nozzle diameter of an extruder or the like, or by changing the strand diameter.
[0169] The length of the pellets is not particularly limited, but is preferably 2 to 4 mm, more preferably 2.5 to 4.0 mm or less.
[0170] [Polyamide film]
[0171] The polyamide film comprises a polyamide resin composition. The polyamide film may be an unstretched polyamide film or a stretched polyamide film obtained by stretching the unstretched polyamide film. From the viewpoint of mechanical strength, the stretched polyamide film is preferred.
[0172] The method for manufacturing the polyamide film is not particularly limited, and for example, a known manufacturing method can be applied. For example, the polyamide resin composition obtained by the manufacturing method 1 is melt-kneaded by using an extruder, extruded into a film-like shape using a die head such as a T die or a hanger die, and cast on a casting roll surface, followed by cooling, thereby manufacturing the polyamide film.
[0173] Alternatively, the melt-kneaded product (D) or the first pellet, the aliphatic polyamide resin (A2) or the second pellet, and any other optional components may be melt-kneaded using an extruder according to the above-mentioned manufacturing method 2, and a polyamide film may be manufactured using the same method. Furthermore, the pellet mixture may be melt-kneaded using an extruder or the like, and a polyamide film may be manufactured using the same method.
[0174] The polyamide film can be stretched to form a stretched film. In this case, the polyamide film can be uniaxially stretched to form a uniaxially stretched film, or can be biaxially stretched (simultaneous biaxial stretching or sequential biaxial stretching) to form a biaxially stretched film.
[0175] The stretching method is not particularly limited, and examples thereof include uniaxial stretching based on a heated roller, simultaneous biaxial stretching based on a tube method, and a sequential biaxial stretching method based on a heated roller and a tenter. The temperature of the heated roller is not particularly limited, and can be set in the range of 35°C to 130°C, and can be appropriately selected according to the material of the polyamide film and the target stretching ratio. Regarding the stretching ratio, there are stretching ratios in the extrusion direction (MD) of the film and in the direction perpendicular to the extrusion direction (TD) of the film. The stretching ratio in the extrusion direction of the film is not particularly limited, and is preferably 2 times or more, more preferably 2 to 6 times, and particularly preferably 2.5 to 5 times. The stretching ratio in the direction perpendicular to the extrusion direction of the film is not particularly limited, and is preferably 2 times or more, more preferably 2 to 6 times, and particularly preferably 2.5 to 5 times. The stretching ratio can be adjusted according to the purpose.
[0176] The thickness of the film is not particularly limited and can be appropriately selected according to the purpose, etc. In the case of a single-layer polyamide film, the thickness of the film can be, for example, 10 μm to 300 μm in the case of an unstretched film and 5 μm to 100 μm in the case of a stretched film.
[0177] Polyamide films exhibit excellent pinhole resistance. Specifically, pinhole resistance can be evaluated as follows: using a Gelbo flex tester (manufactured by TESTER SANGYO) in accordance with MIL-B-131C, an unstretched polyamide film is subjected to 1000 bending tests at 5°C, the film is placed on a recording paper, and then ink is applied. The number of black spots recorded on the recording paper is measured to evaluate the pinhole resistance. The number of black spots measured is preferably 100 or less / 0.03m 2 , more preferably 80 or less / 0.03m 2 , more preferably less than 70 / 0.03m 2 .
[0178] In addition, the polyamide film shows the characteristic of no deterioration in appearance caused by film gel. Specifically, the film gel number can be evaluated using a fisheye counter manufactured by FUTEC. Specifically, for an unstretched film obtained by extruding a polyamide resin composition into a thickness of 40 μm under the conditions of a barrel temperature of 190°C, 230°C and 250°C, a connector temperature of 250°C, a die temperature of 250°C, a screw speed of 25 rpm and a pulling speed of 3.0 m / min when the extruder barrel area is divided into three parts, the fisheye counter is used to measure the number of gels per 0.04 m online. 2 The number of thin film gels with a diameter of 50 μm or more is preferably 100 or less / 0.04 m 2 , preferably less than 80 / 0.04m 2 , more preferably less than 70 / 0.04m 2 .
[0179] The haze rate of the polyamide film is preferably 25% or less, more preferably 15% or less, and further preferably 10% or less. Here, the haze rate of the polyamide film is measured in accordance with ASTM D-1003.
[0180] The gloss value of the polyamide film is preferably 50% or more, more preferably 80% or more, and even more preferably 100% or more. Here, the gloss value of the polyamide film is measured in accordance with ASTM D-523.
[0181] [Laminated film]
[0182] The laminated film contains at least one layer (also referred to as a polyamide film layer) comprising a polyamide resin composition. The method for manufacturing the laminated film can include a method including laminating other layers on one or both sides of the aforementioned polyamide film. The lamination method is not particularly limited, and the coextrusion method, extrusion lamination method, dry lamination method, etc. described in Japanese Patent Publication No. 2011-225870 can be listed. From the viewpoint of economy, the coextrusion method is preferably used. The laminated film manufactured can be stretched to form a stretched laminated film. In this case, the laminated film manufactured can be uniaxially stretched to form a uniaxially stretched film laminate, or biaxially stretched (simultaneous biaxial stretching or sequential biaxial stretching) can be performed to form a biaxially stretched film laminate. The stretching method and the stretching ratio are as described in the polyamide film.
[0183] (Blown Film Forming)
[0184] The laminated film can be manufactured by a molding method such as air-cooled inflation molding or water-cooled inflation molding. Among them, the air-cooled inflation method has simple equipment and can easily change the film width by simply adjusting the air supply ratio, so the workability is good and the film can be manufactured with good productivity.
[0185] The conditions for forming a film by air-cooled inflation molding are not particularly limited, and the molding temperature is preferably above the melting point of the raw resin used and below 300°C. The molding temperature can be set to 230°C to 260°C, for example. In addition, the inflation ratio refers to the ratio of the maximum diameter of the bubble to the diameter of the die head, and the inflation ratio is preferably 1.1 to 3.0, and more preferably 1.2 to 2.5. The pulling speed is determined according to the thickness, width and extrusion amount of the film, and can be adjusted within the range that can maintain the stability of the film. Generally speaking, it is preferably 1 to 150 m / min, and more preferably 5 to 100 m / min.
[0186] (Other layers)
[0187] As other layers, there is no particular limitation as long as the laminated film exhibits the effect of the polyamide film, and examples thereof include a polyolefin layer and an adhesive layer. Here, the adhesive layer is appropriately selected for the purpose of improving the adhesion and formability of the polyamide film layer and the polyolefin layer described in the present invention. It should be noted that the polyamide film layer described in the present invention is not a polyolefin layer and an adhesive layer.
[0188] The polyolefin layer and the adhesive layer may contain additives. As the additives, the substances exemplified in other components (C) can be used.
[0189] As the polyolefin constituting the polyolefin layer, non-polar polyolefins such as low-density polyethylene, linear low-density polyethylene, high-density polyethylene, ethylene / α-olefin copolymers with more than 3 carbon atoms, propylene homopolymers, and propylene / α-olefin copolymers with more than 4 carbon atoms can be listed; ethylene / acrylic acid copolymers, ethylene / vinyl acetate copolymers, ethylene / acrylate copolymers, ethylene / methacrylic acid copolymers, etc. Among them, from the viewpoint of food packaging use, non-polar polyolefins and ethylene / vinyl acetate copolymers are preferred, and linear low-density polyethylene is more preferred. If the polyolefin layer is a layer of non-polar polyolefin, there is a tendency for the water vapor barrier of the laminated film to be further improved. If the polyolefin layer is a layer of ethylene / vinyl acetate copolymer, there is a tendency for the oxygen permeability of the laminated film to be further reduced. The laminated film comprising at least a polyamide film layer and a polyolefin layer can not only be suitably used for food packaging purposes, but also has excellent material recyclability of the film waste.
[0190] The adhesive layer is composed of an adhesive resin or an adhesive. As the adhesive resin, there can be listed acid-modified polyolefin resins such as maleic acid-modified polyethylene grafted with at least one monomer selected from unsaturated carboxylic acids and their derivatives, ionomers, ethylene / acrylic acid copolymers, ethylene / methacrylic acid copolymers, etc. As the adhesive, there can be listed, for example, solvent-based adhesives, solvent-free adhesives, etc. In addition to adhesives that use a single component to bond, there are also adhesives that mix two components to bond. As the adhesive, there can be listed epoxy adhesives, carbamate adhesives, etc., preferably carbamate adhesives. As carbamate adhesives, there can be listed adhesives of aromatic ethers, aliphatic esters, aromatic esters, etc.
[0191] (Layer composition)
[0192] As the specific layer composition of the laminated film, two layers of a polyamide film layer and a polyolefin layer can be listed; three layers of a polyamide film layer, an adhesive layer and a polyolefin layer; at least three layers consisting of a polyamide film layer and a polyolefin layer, and one or more other layers selected from the group consisting of a polyamide film layer, an adhesive layer and a polyolefin layer; at least four layers consisting of a polyamide film layer, a polyolefin layer and an adhesive layer, and one or more other layers selected from the group consisting of a polyamide film layer, an adhesive layer and a polyolefin layer, etc. Among them, from the viewpoint of food packaging use, it is preferred to contain a laminated film having at least three layers obtained by sequentially stacking a layer comprising a polyamide resin composition, an adhesive layer, and a polyolefin layer; or a laminated film having at least five layers obtained by sequentially stacking an adhesive layer and a polyolefin layer on both sides of a layer comprising a polyamide resin composition. In addition, when the laminated film is an unstretched laminated film and a deep-drawn packaging film, it is preferred to have a polyolefin layer in the inner layer. Here, in the laminated film, the layer in contact with the outside air is the outer layer, and the layer in contact with the food to be packaged is the inner layer. In addition, the layer containing the polyamide resin composition may be a biaxially stretched layer.
[0193] (thickness)
[0194] The thickness of the laminated film is not particularly limited and can be selected according to the purpose. The thickness of each layer of the polyamide film in the laminated film can be set to 1 to 300 μm, preferably 2 to 100 μm, and more preferably 5 to 80 μm. The thickness of each layer of the polyolefin layer can be appropriately selected according to the purpose, for example, preferably in the range of 8 to 120 μm. The thickness of each layer of the adhesive layer can be selected according to the purpose, for example, preferably in the range of 1 to 100 μm. The total film thickness of the laminated film is not particularly limited, preferably 5 to 500 μm, more preferably 20 to 300 μm, and particularly preferably 50 to 200 μm.
[0195] [use]
[0196] The polyamide resin composition and the pellet mixture can be used as raw materials for various molded products. The molded products containing the polyamide resin composition can be used for a wide range of applications such as packaging films such as food packaging, automobile components, computers and related equipment, optical equipment components, electrical / electronic equipment, information / communication equipment, precision equipment, civil / construction supplies, medical supplies, household products, etc., and are suitable for packaging films, and are particularly useful for food packaging films.
[0197] The polyamide film and the laminated film do not have deterioration in appearance due to film gelation and are excellent in pinhole resistance in a low temperature environment. Therefore, the polyamide film and the laminated film can be suitably used for packaging of articles, especially for food packaging.
[0198] Unstretched polyamide film and unstretched laminated film have excellent deep drawing properties, and therefore, can be suitably used as food packaging films, especially deep drawing packaging films for food. When unstretched polyamide film is used as deep drawing packaging film, food is stored in a deep drawing packaging base material obtained by deep drawing the film, and a cover material is used for packaging. As the food stored in the deep drawing packaging base material, sliced foods such as ham and cheese can be listed. The cover material is not particularly limited and can be appropriately selected according to the purpose.
[0199] Stretched polyamide films and stretched laminated films are excellent in mechanical strength and oxygen barrier properties and are therefore useful as food packaging films for filling and packaging semi-fluid foods such as sausages (paste), solid foods such as processed meat and ham, and the like.
[0200] In particular, a laminated film containing at least a layer comprising a polyamide resin composition and a polyolefin layer, and a laminated film in which a layer comprising a polyamide resin composition, an adhesive layer and a polyolefin layer are laminated in this order are not only suitably used for food packaging purposes, but also have excellent material recyclability of film waste and are useful.
[0201] Example
[0202] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples. However, the present invention is not limited to these Examples and can be implemented with appropriate modifications within the scope of the present invention.
[0203] [Measurement of Physical Properties of Raw Materials, First Pellets, Second Pellets, and Polyamide Resin Composition]
[0204] The following physical properties were evaluated for each of the raw materials, the first pellets, the second pellets, and the polyamide resin composition.
[0205] 1. Relative viscosity
[0206] Regarding the aliphatic polyamide resin (A), according to JIS K 6920, 1 g of the polyamide resin was dissolved in 100 ml of 96% sulfuric acid, and the relative viscosity at 25° C. was measured.
[0207] 2.DSC measurement
[0208] Each raw material and polyamide resin composition was measured using a differential scanning calorimeter (DSC). The sample was heated to 280°C in an air atmosphere, maintained at this temperature for 5 minutes, and then the temperature was reduced to 0°C at a cooling rate of 20°C / min, and the peak temperature of the exothermic peak at this time was set as the crystallization temperature. Next, the sample was heated from 0°C to 280°C at a rate of 20°C / min, and the peak temperature of the endothermic peak at this time was set as the melting peak temperature (melting point).
[0209] 3.MFR (230℃ and load 2.16kg)
[0210] The MFR of each of the raw material, the first pellet, the second pellet, and the polyamide resin composition was measured in accordance with ASTM D1238 under the conditions of 230° C. and a load of 2.16 kg.
[0211] 4. Amino acid concentration
[0212] For aliphatic polyamide resin (A), a prescribed amount of polyamide resin was added to a conical flask with a piston, and 40 mL of a pre-prepared solvent: phenol / methanol (volume ratio of 7 / 3) was added, and then stirred and dissolved using a magnetic stirrer. Thymol blue was used as an indicator, and titration was performed with 1 / 50N hydrochloric acid to obtain the terminal amino concentration (eq / g). The same operation was performed for the unstretched polyamide film a of Example 5 and Comparative Examples 4 and 8 to obtain the amino concentration (eq / g).
[0213] 5. Carboxyl concentration
[0214] For the aliphatic polyamide resin (A), a prescribed amount of polyamide resin was added to a three-necked eggplant flask, 40 mL of benzyl alcohol was added, and then immersed in an oil bath set to 180°C under a nitrogen gas flow. The stirring motor installed on the top was used for stirring and dissolving, and phenolphthalein was used as an indicator. The terminal carboxyl concentration (eq / g) was titrated with a 1 / 20N sodium hydroxide solution. The unstretched polyamide film a of Example 5 and Comparative Examples 4 and 8 was also operated in the same manner to obtain the carboxyl concentration (eq / g).
[0215] 6. Molecular weight measured by GPC
[0216] GPC measurement was performed using HLC-8320GPO manufactured by Tosoh Corporation under the following conditions, and the number average molecular weight Mn and the weight average molecular weight Mw were calculated in terms of PMMA.
[0217] Column: TSKgel Super AW3000+TSKgel Super AW5000
[0218] Eluent: 10 mM CF3CΟΟHNa / TFE
[0219] Detector: RI
[0220] Temperature: 40℃
[0221] Flow rate: 0.3 ml / min for sample, 0.15 ml / min for control
[0222] Sample concentration: about 0.1wt / vol%
[0223] Injection volume: 20μl
[0224] [Raw materials used]
[0225] The raw materials used in Examples and Comparative Examples are as follows.
[0226] (1) Aliphatic polyamide resin (A)
[0227] Polyamide resin (A-1): polyamide 6 manufactured by UBE (relative viscosity: 2.2; melting point: 220°C; MFR measured according to ASTM D1238 at 230°C and a load of 2.16 kg: 60.0 g / 10 min; terminal amino group concentration: 3.3×10 -5 eq / g)
[0228] Polyamide resin (A-2): manufactured by UBE, polyamide 6 (relative viscosity: 2.5; melting point: 220°C; MFR measured according to ASTM D1238 at 230°C and a load of 2.16 kg: 40.4 g / 10 min; terminal amino group concentration: 4.5×10 -5 eq / g)
[0229] Polyamide resin (A-3): manufactured by UBE, polyamide 6 (relative viscosity: 2.7; melting point: 220°C; MFR measured according to ASTM D1238 at 230°C and a load of 2.16 kg: 25.0 g / 10 min; terminal amino group concentration: 4.0×10 -5 eq / g)
[0230] Polyamide resin (A-4): manufactured by UBE, polyamide 6 (relative viscosity: 3.0; melting point: 220°C; MFR measured according to ASTM D1238 at 230°C and a load of 2.16 kg: 15.0 g / 10 min; terminal amino group concentration: 3.0×10 -5 eq / g)
[0231] Polyamide resin (A-5): manufactured by UBE, polyamide 6 (relative viscosity: 3.4; melting point: 220°C; MFR measured according to ASTM D1238 at 230°C and a load of 2.16 kg: 6.4 g / 10 min; terminal amino group concentration: 4.0×10 -5 eq / g)
[0232] (2) Acid-modified ethylene / α-olefin copolymer (B)
[0233] Maleic anhydride-modified ethylene / 1-hexene copolymer (B-1): F3000 manufactured by Ube Maruzen Polyethylene Co., Ltd. (melting point: 115°C; MFR measured at 230°C and a load of 2.16 kg according to ASTM D1238: 8.5 g / 10 min; maleic anhydride modification rate: 1 mass %)
[0234] Maleic anhydride-modified ethylene / 1-octene copolymer (B-2): AFFINITY GA1000R manufactured by Dow Inc. (melting point: 68° C.; MFR measured at 230° C. and a load of 2.16 kg according to ASTM D1238: 660.0 g / 10 min; maleic anhydride modification rate: 1% by mass)
[0235] Example 1
[0236] To 40% by mass of polyamide resin (A-1) as the first aliphatic polyamide resin (A1), 10% by mass of maleic anhydride-modified ethylene / 1-hexene copolymer (B-1) was added, and melt-kneading was performed using a twin-screw mixer ZSK32McPlus (manufactured by Coperion, with a screw diameter of 32 mm) at a barrel temperature of 230°C, a screw speed of 500 rpm, and a discharge rate of 75 kg / h to produce a first pellet. Next, a polyamide resin (A-5) was used as the second aliphatic polyamide resin (A2) to produce a second pellet. Finally, 50% by mass of the first pellet and 50% by mass of the second pellet were dry-mixed to obtain a pellet mixture. The formulation of the pellet mixture of Example 1 is shown in Table 1.
[0237] Using the pellet mixture of Example 1, unstretched polyamide films a, c and d and a biaxially stretched polyamide film b were produced in the following manner.
[0238] Unstretched polyamide film
[0239] The pellet mixture of Example 1 was used to prepare an unstretched polyamide film a having a thickness of 50 μm using a 40 mmφEx T-die film forming machine manufactured by Plastics Technology Laboratories, Inc.
[0240] Biaxially stretched polyamide film
[0241] The pellet mixture of Example 1 was used to prepare an unstretched polyamide film having a thickness of 100 μm using a 40 mm φEx T-die film forming machine manufactured by Plastics Technology Laboratories, Inc. The unstretched polyamide film thus obtained was stretched to a total of 9.0 times (3.0 times in the longitudinal direction and 3.0 times in the transverse direction) at a stretching temperature of 100° C. using a biaxial stretching machine manufactured by Iwamoto Seisakusho Co., Ltd. to prepare a biaxially stretched polyamide film b having a thickness of 15 μm.
[0242] Unstretched polyamide film
[0243] The pellet mixture of Example 1 is supplied to a single-screw extruder equipped with a T-die (25 mmφEx T-die film forming machine manufactured by GM ENGINEERING), and an unstretched polyamide film c with a thickness of 40 μm is produced under the conditions that the barrel temperature when the extruder barrel area is divided into three parts is 190°C, 230°C and 250°C, the connector temperature is 250°C, the die head temperature is 250°C, the screw speed is 25 rpm and the pulling speed is 3.0 m / min.
[0244] Unstretched polyamide film
[0245] The pellet mixture of Example 1 was supplied to a single screw extruder equipped with a T-die (40 mmφEx T-die film molding machine manufactured by Plastics Technology Laboratories, Inc.) to produce an unstretched polyamide film d having a thickness of 30 μm.
[0246] Examples 2 to 7 and Comparative Examples 1 to 7
[0247] Except having changed the kind and ratio of each component as shown in Table 1, the same operation as in Example 1 was carried out to obtain pellet mixtures and polyamide films a to d of Examples 2 to 7 and Comparative Examples 1 to 7.
[0248] Comparative Example 8
[0249] Unstretched polyamide films a, c and d and biaxially stretched polyamide film b were prepared in the same manner as in Example 1 except that only pellets of polyamide resin (A-5) were used. The formulation of the pellets of Comparative Example 8 is shown in the column of the second pellet in Table 1.
[0250] Comparative Example 9
[0251] According to the formulation of 90 mass % of pellets of polyamide resin (A-5) and 10 mass % of pellets of maleic anhydride-modified ethylene / 1-hexene copolymer (B-1), a 50 μm thick unstretched polyamide film a was produced using a 40 mmφEx T-die film forming machine manufactured by Plastics Technology Laboratories, Inc. The resin pressure during film forming was 5.1 MPa. The obtained film produced significant aggregates and could not be formed into a normal film. Therefore, the remaining film production and evaluation could not be carried out.
[0252] Table 1 shows the formulations of Examples 1 to 7 and Comparative Examples 1 to 9 and various physical properties of the obtained polyamide resin compositions.
[0253] [Table 1]
[0254]
[0255] The amino group concentration and carboxyl group concentration of the unstretched polyamide films a of Example 5 and Comparative Examples 4 and 8 were measured.
[0256] [Table 2]
[0257]
[0258] [evaluate]
[0259] The following properties were evaluated for each of the polyamide films produced in Examples 1 to 7 and Comparative Examples 1 to 8. Table 3 shows the evaluation results.
[0260] 1. Film forming resin pressure
[0261] When making an unstretched polyamide film a, the resin pressure at the outlet of the T-die film forming machine is measured. If the resin pressure is 0.5 to 4.0 MPa, it is judged that the formability is good, and if it is 1.0 to 3.0 MPa, it is judged that the formability is particularly excellent. By being in the above range, the production speed of film forming can be increased, and the occurrence of resin leakage from the forming machine can be suppressed.
[0262] 2. Haze value (haze rate)
[0263] The haze values (haze ratio) of the unstretched polyamide film a and the biaxially stretched polyamide film b were measured using a haze meter manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with ASTM D-1003. If the haze ratio is 25% or less, it is judged that there is no problem in practical use, if it is 15% or less, it is judged that the transparency is excellent, and if it is 10% or less, it is judged that the transparency is particularly excellent.
[0264] 3. Glossiness (gloss value)
[0265] The glossiness (gloss value) of the unstretched polyamide film a and the biaxially stretched polyamide film b was measured using a digital variable angle gloss meter manufactured by Suga Test Instruments in accordance with ASTM D-523. If the gloss value is 50% or more, it is judged that there is no problem in practical use, if it is 80% or more, it is judged that the gloss is excellent, and if it is 100% or more, it is judged that the gloss is particularly excellent.
[0266] 4. Puncture test
[0267] For the unstretched polyamide film a and the biaxially stretched polyamide film b, after being stored at 23°C and 50% RH for 1 day, the elongation at break and the maximum point load were measured in the same environment according to JAS (P-1019) using a needle with a diameter of 1.0φ and a tip shape of 0.5R. The acceptance standard for the maximum point load was set to more than 5.0N, and if it was 6.0N or more, it was judged that the puncture strength was particularly excellent.
[0268] 5. Friction coefficient
[0269] For the unstretched polyamide film a and the biaxially stretched polyamide film b, after being stored at 23°C and 50% RH for 1 day, the static friction coefficient and the dynamic friction coefficient were measured 5 times in the same environment according to ASTM D-1894, and the average values were obtained. It should be noted that the friction coefficient of the biaxially stretched polyamide film b of Comparative Example 8 was too high and therefore could not be measured.
[0270] The acceptance criteria for the static friction coefficient and the dynamic friction coefficient of the unstretched polyamide film a were each set to 1.0 or less.
[0271] 6. Number of film gels produced
[0272] The number of film gels generated was measured for the unstretched polyamide films c obtained in Examples 1 to 7 and Comparative Examples 1 to 3, 7 and 8. The number of film gels generated was measured for the unstretched polyamide films c using a fisheye counter manufactured by FUTEC. 2 The number of thin film gels with diameters of 50 to 99 μm, 100 to 199 μm, and 200 μm or more was counted to evaluate the number of thin film gels produced (pieces / 0.04 m 2 In Table 3, the number of thin film gels produced is the average value of the results of 50 measurements. The acceptance criterion for thin film gels is the number of gels of 50 to 99 μm: 100 or less / 0.04 m 2 .
[0273] In addition, since the unstretched polyamide films c of Comparative Examples 4 to 6 produced significant aggregates, the number of film gels produced was not evaluated.
[0274] 7. Pinhole resistance in low temperature environment
[0275] The unstretched polyamide films d obtained in Examples 1 to 7 and Comparative Examples 1 to 8 were subjected to a bending test at 5°C for 1000 times using a Gelpo-Frankx tester with a thermostatic chamber manufactured by TESTER SANGYO Co., Ltd. in accordance with MIL-B-131C. The film after the bending test was placed on a recording paper, and then ink was applied to penetrate the recording paper, and the number of recorded black dots was counted. Pinhole resistance was determined according to the following criteria.
[0276] ◎: The number of black spots is less than 70 / 0.03m 2
[0277] ○: The number of black spots is more than 70 / 0.03m 2 And less than 100 / 0.03m 2
[0278] ×: The number of black spots exceeds 100 / 0.03m 2
[0279] 8. Reusability
[0280] Using the pellet mixture or pellets obtained in Examples 1 to 7 and Comparative Examples 1 to 8, three types of three-layer co-extrusion air-cooled multilayer inflation molding machines (die head diameter of 100 mmφ) manufactured by Doctecolin Co., Ltd. were used to obtain a laminated film with a thickness of 100 μm consisting of three layers of a polyamide resin composition layer of 20 μm, an adhesive layer of 10 μm, and a polyethylene layer of 70 μm. The adhesive layer used ADMER (registered trademark) LF128 (acid-modified polyolefin resin) manufactured by Mitsui Chemicals, Inc., and the polyethylene layer used F022NH (low-density polyethylene resin) manufactured by Ube Maruzen Polyethylene Co., Ltd. The obtained laminated film was cut and made into a thin sheet. Next, 20% by mass of the above-mentioned flakes were added to 80% by mass of the polyamide resin (A-5), and melt-kneaded using a twin-screw kneader ZSK32McPlus (manufactured by Coperion, with a screw diameter of 32 mm) at a barrel temperature of 230° C., a screw speed of 500 rpm, and a discharge rate of 75 kg / h to obtain recycled pellets. The recycled pellets were supplied to a single-screw extruder equipped with a T-die (a 40 mmφEx T-die film forming machine manufactured by Plastics Technology Laboratories, Inc.) to prepare an unstretched polyamide film e having a thickness of 50 μm, and its appearance was visually confirmed and evaluated, and the recyclability was judged according to the following criteria.
[0281] 5: There is no unevenness on the film, no particles are visually confirmed, the transparency is extremely good, and the recyclability is particularly excellent.
[0282] 4: There is no unevenness on the film, there are few particles, the transparency is good, and the recyclability is further excellent.
[0283] 3: There is no unevenness on the film. Although particles are confirmed, there is a sense of transparency and the recyclability is excellent.
[0284] 2: There are many particles and unevenness on the film, lack of transparency, and poor recyclability.
[0285] 1: It is difficult to perform normal film molding and the recyclability is significantly poor.
[0286] The evaluation results of various films of Examples 1 to 7 and Comparative Examples 1 to 8 are shown in Table 3. In Table 3, "many particles" means that film gelation occurred frequently, and therefore the number of film gels generated was not evaluated, and "unable to measure" means that it could not be measured.
[0287] [Table 3]
[0288]
[0289] According to Table 3, the compositions of Examples 1 to 7 can provide films with excellent transparency, puncture strength, friction coefficient and pinhole resistance without deterioration of appearance caused by film gelation, and excellent material recyclability. In Examples 1 to 7, a pellet mixture containing a first pellet and a second pellet is melt-kneaded to produce a film, wherein the first pellet contains a first aliphatic polyamide resin (A1) and an ethylene / α-olefin copolymer having 3 to 8 carbon atoms (B) having a functional group in a predetermined ratio, and the second pellet contains a second aliphatic polyamide resin (A2), so that each component can be uniformly mixed and the generation of film gelation can be suppressed, and the film molding resin pressure is low and the moldability is also excellent.
[0290] Although the aliphatic polyamide resin (A) and the ethylene / α-olefin copolymer having 3 to 8 carbon atoms (B) having a functional group are contained in a predetermined ratio, in Comparative Examples 1 to 6 in which the number average molecular weight Mn of the polyamide resin composition exceeds 46,000, many films have gels generated, which is poor. Furthermore, in Comparative Examples 3 to 6, regarding the appearance of the formed film in the evaluation of recyclability, a large amount of particles and unevenness exist on the film, and the transparency is poor, and the material recyclability is also poor.
[0291] In Comparative Example 7, in which the number average molecular weight Mn of the polyamide resin composition exceeded 46,000 and the first melting peak temperature of the composition was not observed, a large number of film gels were generated and the maximum point load in the puncture test was low. In Comparative Example 8, which was composed only of aliphatic polyamide resin (A), the film had a high friction coefficient and poor pinhole resistance and material recyclability.
[0292] In Comparative Example 9, in which the number average molecular weight Mn of the polyamide resin composition exceeds 46,000 and the first pellet is not prepared, but the pellets of the aliphatic polyamide resin (A) and the copolymer (B) are directly put into a T-die film molding machine for molding, the resin pressure during film molding is high, the obtained film produces significant aggregates, and a normal film cannot be molded.
[0293] Industrial Applicability
[0294] The film obtained from the polyamide resin composition of the present invention is particularly suitable for use in food packaging and the like, and the waste of the film is excellent in material recyclability and is useful.
Claims
1. A polyamide resin composition, wherein The polyamide resin composition comprises 70 to 95% by mass of an aliphatic polyamide resin (A), 5 to 30% by mass of an ethylene / α-olefin copolymer having 3 to 8 carbon atoms having a functional group (B), and 0 to 5% by mass of other components (C), based on 100% by mass of the polyamide resin composition. In the aliphatic polyamide resin (A), the ratio of the number of methylene groups to the number of amide groups is 3 or more and 11 or less, When the number average molecular weight and the weight average molecular weight of the polyamide resin composition measured by GPC are respectively defined as Mn and Mw, Mn is 25,000 to 46,000, and Mw / Mn is 1.5 to 3.
0.
2. The polyamide resin composition according to claim 1, wherein The aliphatic polyamide resin (A) is an aliphatic homopolyamide.
3. The polyamide resin composition according to claim 1 or 2, wherein The aliphatic polyamide resin (A) is at least one selected from the group consisting of polyamide 4, polyamide 6, polyamide 11, polyamide 12, polyamide 46, polyamide 410, polyamide 56, polyamide 66, polyamide 510, polyamide 512, polyamide 610, polyamide 612, polyamide 1010, and polyamide 1012.
4. The polyamide resin composition according to claim 1 or 2, wherein The number average molecular weight Mn of the polyamide resin composition is 35,000 to 46,000.
5. The polyamide resin composition according to claim 1 or 2, wherein The first melting peak temperature measured from the DSC curve when the composition is heated from 0°C to 280°C at a rate of 20°C / min in an air atmosphere is in the range of 70 to 120°C, and the second melting peak temperature is in the range of 150 to 260°C.
6. The polyamide resin composition according to claim 1 or 2, wherein The concentration of amino groups in the composition is 2.0×10 -5 ~3.5×10 -5 eq / g, the concentration of carboxyl groups is 4.5×10 -5 ~6.0×10 -5 eq / g.
7. The polyamide resin composition according to claim 1 or 2, wherein The copolymer (B) is an ethylene / propylene copolymer, an ethylene / 1-butene copolymer or an ethylene / 1-hexene copolymer having a group derived from maleic anhydride.
8. The polyamide resin composition according to claim 1 or 2, which is substantially free of silicon dioxide.
9. The polyamide resin composition according to claim 1 or 2, wherein For an unstretched film obtained by extruding a polyamide resin composition into a 40 μm thick film under the conditions of a barrel temperature of 190° C., 230° C. and 250° C. when the barrel area of the extruder is divided into three parts, a joint temperature of 250° C., a die temperature of 250° C., a screw speed of 25 rpm and a pulling speed of 3.0 m / min, the number of gels of 50 to 99 μm in the gel measurement is 100 or less / 0.04 m 2 . 10 . A polyamide film comprising the polyamide resin composition according to claim 1 or 2 . 11 . A laminated film comprising three layers, wherein a layer comprising the polyamide resin composition according to claim 1 or 2, an adhesive layer, and a polyolefin layer are laminated in this order.
12. A laminated film comprising five layers, wherein: An adhesive layer and a polyolefin layer are sequentially laminated on both surfaces of the layer comprising the polyamide resin composition according to claim 1 or 2.
13. The laminated film according to claim 11, wherein The layer comprising the polyamide resin composition is a biaxially stretched layer.
14. The laminated film according to claim 11, which is used for food packaging.
15. A pellet mixture comprising a first pellet comprising a first aliphatic polyamide resin (A1) and an ethylene / α-olefin copolymer having 3 to 8 carbon atoms (B) having a functional group, and a second pellet comprising a second aliphatic polyamide resin (A2). 100% by mass of the first pellet comprises 60 to 90% by mass of the first aliphatic polyamide resin (A1), 10 to 40% by mass of the ethylene / α-olefin copolymer having 3 to 8 carbon atoms (B) having a functional group, and 0 to 5% by mass of other components (C), wherein the MFR of the first pellet measured at 230° C. and a load of 2.16 kg according to ASTM D1238 is 1 to 40 g / 10 minutes, The second aliphatic polyamide resin (A2) has a relative viscosity of 2.5 to 5.0 when 1 g of the polyamide resin is dissolved in 100 ml of 96% sulfuric acid according to JIS K 6920 at 25° C., a melting point of 150 to 260° C., and an MFR of 1 to 20 g / 10 minutes when measured at 230° C. and a load of 2.16 kg according to ASTM D1238. In the aliphatic polyamide resin (A1) and the aliphatic polyamide resin (A2), the ratio of the number of methylene groups to the number of amide groups is 3 or more and 11 or less, and the melting point of the copolymer (B) is 70 to 120° C., The pellet mixture is melt-kneaded to form a kneaded product containing 70 to 95% by weight of the first aliphatic polyamide resin (A1) and the second aliphatic polyamide resin (A2), 5 to 30% by weight of an ethylene / α-olefin copolymer having 3 to 8 carbon atoms (B) having a functional group, and 0 to 5% by weight of other components (C). When the number average molecular weight and the weight average molecular weight of the kneaded product measured by GPC are respectively defined as Mn and Mw, Mn is 25,000 to 46,000, and Mw / Mn is 1.5 to 3.
0.
16. The first pellet is used for mixing with the second pellet in the manufacture of the pellet mixture according to claim 15.
17. The second pellets used for mixing with the first pellets in the manufacture of the pellet mixture according to claim 15.
Citation Information
Patent Citations
Polyamide resin compound and polyamide film
JP2000109685A
Polyamide resin composition for film and polyamide film comprising the same
JP2011225870A
Composition, method, and article produced by compounding polyamide with olefin-maleic anhydride polymer
JP2014503003A
Olefin-maleic anhydride copolymer composition and method of use thereof
JP2015525813A
Self-renewable barrier packaging
JP2018502743A